Correlation Between Static Radiographic Measurements and Intersegmental Angular Measurements During Gait Using a Multisegment Foot Model. (January 2015) - Lee, Dong Yeon; Seo, Sang Gyo; Kim, Eo Jin; Kim, Sung Ju; Lee, Kyoung Min; Farber, Daniel C.; Chung, Chin Youb; Choi, In Ho
Background: Radiographic examination is a widely used evaluation method in the orthopedic clinic. However, conventional radiography alone does not reflect the dynamic changes between foot and ankle segments during gait. Multiple 3-dimensional multisegment foot models (3D MFMs) have been introduced to evaluate intersegmental motion of the foot. In this study, we evaluated the correlation between static radiographic indices and intersegmental foot motion indices. Methods: One hundred twenty-five females were tested. Static radiographs of full-leg and anteroposterior (AP) and lateral foot views were performed. For hindfoot evaluation, we measured the AP tibiotalar angle (TiTA), talar tilt (TT), calcaneal pitch, lateral tibiocalcaneal angle, and lateral talcocalcaneal angle. For the midfoot segment, naviculocuboid overlap and talonavicular coverage angle were calculated. AP and lateral talo-first metatarsal angles and metatarsal stacking angle (MSA) were measured to assess the forefoot. Hallux valgus angle (HVA) and hallux interphalangeal angle were measured. In gait analysis by 3D MFM, intersegmental angle (ISA) measurements of each segment (hallux, forefoot, hindfoot, arch) were recorded. Results: ISAs at midstance phase were most highly correlated with radiography. Significant correlations were observed between ISA measurements using MFM and static radiographic measurements in the same segment. In the hindfoot, coronal plane ISA was correlated with AP TiTA ( P < .001) and TT ( P = .018). In the hallux, HVA was strongly correlated with transverse ISA of the hallux ( P < .001). Conclusion: The segmental foot motion indices at midstance phase during gait measured by 3D MFM gait analysis were correlated with the conventional radiographic indices. Clinical Relevance: The observed correlation between MFM measurements at midstance phase during gait and static radiographic measurements supports the fundamental basis for the use of MFM in analysis of dynamic motion of foot segment during gait.